2022
DOI: 10.1007/s11739-022-02950-w
|View full text |Cite
|
Sign up to set email alerts
|

Residual symptoms, lung function, and imaging findings in patients recovering from SARS-CoV-2 infection

Abstract: Symptoms following acute COVID-19 infection are common, but their relationship to initial COVID-19 severity is unclear. We hypothesize that residual symptoms are related to disease severity, and severe acute COVID-19 infection is more likely to cause residual pulmonary damage. This study aims to evaluate symptoms, lung function, and abnormal imaging within 3 months following COVID-19 infection, and to determine whether they are related to initial disease severity. A cross-sectional study was carried out at a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Results of all included studies can be found in Table S1 . All studies included a population with a mean or median age between 47 and 66 years and most studies had an equal distribution of males and females.The majority of the studies were conducted in Europe (n = 26) [ [3] , [4] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ],49,51,56,60,62,65,66,67,69,70,74,76,77,79,80,81,83,84], six were conducted in North America [ [59] , [60] , [61] , [62] , [63] , [64] ], four in South America [ [65] , [66] , [67] , [68] ] and eleven in Asia [ [16] , [17] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. The population of the studies varied between 17 and 1733 with a mean of 177 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Results of all included studies can be found in Table S1 . All studies included a population with a mean or median age between 47 and 66 years and most studies had an equal distribution of males and females.The majority of the studies were conducted in Europe (n = 26) [ [3] , [4] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ],49,51,56,60,62,65,66,67,69,70,74,76,77,79,80,81,83,84], six were conducted in North America [ [59] , [60] , [61] , [62] , [63] , [64] ], four in South America [ [65] , [66] , [67] , [68] ] and eleven in Asia [ [16] , [17] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. The population of the studies varied between 17 and 1733 with a mean of 177 participants.…”
Section: Resultsmentioning
confidence: 99%
“…More than four studies concluded that initial symptoms of COVID-19 infection are not significantly associated with post-COVID-19 syndrome (Townsend et al 2021 ; Darawshy et al 2022 ; Stengel et al 2021 ; Townsend et al 2020 ; Miyazato et al 2020 ). However, the current study revealed that several symptoms, mainly insomnia, drowsiness, and shortness of breath, are risk factors for long COVID-19 symptoms, with odds ratios >3.…”
Section: Resultsmentioning
confidence: 99%
“…This approach clarified the presence of pulmonary symptoms and may not discern individuals who had their symptoms overestimated based on the questionnaire. Studies demonstrate that pulmonary symptoms were present regardless of initial COVID severity, but patients with severe COVID-19 were more likely to have impairment of lung function ( 32 , 33 ). Also, pulmonary symptoms were presented without impairment of lung function or cardiopulmonary exercise test among COVID-19 survivors ( 33 ).…”
Section: Discussionmentioning
confidence: 99%